Better care through an optimized mental health services continuum (Eastern Townships, Québec, Canada): A systematic and multisource literature review. (31st October 2018) - Roy, Mathieu; Dagenais, Pierre; Pinsonneault, Linda; Déry, Véronique
Summary: Introduction: In 2014, the health authorities of the Eastern Townships (Québec, Canada) commissioned an evaluation of the mental health admission system for adults (GASMA) to identify the best GASMA organizational or structural elements and optimize the mental health services continuum. Methods: To develop better services, seven indicators (ie, accessibility to services, integration of levels of services, user satisfaction, guidance and management time, evaluation tools, professional composition, and interprofessional collaboration) were examined through four evaluation questions. A three‐step systematic and multisource evaluation was realized. A systematic review of the scientific and gray literature was performed. This evaluation also included key informant opinions to contextualize results from this review. Results: Results from 91 scientific articles, 40 gray literature documents, and 10 interviews highlighted determinants and barriers associated with the examined indicators. From these results, 24 preliminary recommendations were formulated and discussed in a steering committee. These recommendations were then weighted and validated. This served to formulate three final recommendations. Conclusion: To optimize the regional mental health services continuum, stakeholders should (1) implement a single‐window access for adults with mental health needs, (2) develop alternative services based on users' needs, and (3) test the effectiveness of new methods, initiatives, and tools.